The Bipolarity of Modern ‘Man’ in the Anthropocene: Ecomodernist Mania as Case for Unmanning Anthropocene Discourse - Kupferschmidt, Philip Douglas (The Trumpeter, 2016)
This paper examines Shellenberger and Nordhaus’ “Evolve: The Case for Modernization as the Road to Salvation” from the perspective of psychopathology. ”Evolve” articulates an all too common denial about the severe implications of the Anthropocene. This denial, I suggest, derives from modern humanity’s wish to save itself from the threats of ecocide and apocalypse without having to change its modernist ways. Upon considering this understandable inclination towards denial, the paper unveils the resultant manic-depressive opposition between ecomodernism and deep ecology. Modern humanity’s respective manic and depressive reactions to these two poles fosters a manic, escapist denial that promotes modernist expansion and limits our capacity to reform Anthropocene discourse and avoid environmental crisis. The analogy between bipolar disorder and the ecomodernism / deep ecology opposition draws from Darian Leader’s Lacanian psychoanalytic account, as well as his phenomenological-psychiatric influences.